2011
DOI: 10.1097/bcr.0b013e318204b3ea
|View full text |Cite
|
Sign up to set email alerts
|

Blood Product Transfusion: Does Location Make a Difference?

Abstract: Early blood product administration during acute blood loss may improve outcomes, yet blood product transfusion for anemia of critical illness has been associated with increased mortality. After major burn injury, patients have two sources of anemia: massive acute blood loss during excision and insidious losses in the intensive care unit (ICU). The purpose of this study was to assess the relationship between the administration of fresh frozen plasma (FFP), platelets, and cryoprecipitate and outcomes in children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Nevertheless, we have determined that erythrocyte, FFP, or albumin transfusion requirements were all associated with the increased risk of mortality in electrical burn patients. Similar to our results, Palmieri et al [25] also defined an association of increased mortality with a blood product use in severe burns in childhood.…”
Section: Discussionsupporting
confidence: 81%
“…Nevertheless, we have determined that erythrocyte, FFP, or albumin transfusion requirements were all associated with the increased risk of mortality in electrical burn patients. Similar to our results, Palmieri et al [25] also defined an association of increased mortality with a blood product use in severe burns in childhood.…”
Section: Discussionsupporting
confidence: 81%
“…16 We reported that burned children receiving FFP had higher mortality and complications. 24 Given the retrospective nature of these studies, associations between FFP and outcome remain tentative, at best. Perhaps, most importantly, none of these studies address FFP transfusion in acute blood loss.…”
Section: Discussionmentioning
confidence: 98%
“…Two large point prevalence studies assessed plasma and platelet transfusion practices in large cohorts of critically ill children but did not independently report results for noncardiac surgical patients (9,16). The remaining analyzed literature included historical registry studies (28-30), a case series (31), an audit (32), prospective cohort studies (12,(33)(34)(35)(36)(37), and retrospective cohort studies (38)(39)(40)(41)(42)(43)(44)(45)(46). (9).…”
Section: ) In Critically Ill Pediatric Patients Undergoing Invasive P...mentioning
confidence: 99%